STUDY ON THE RITUAL ARCHITECTURE OF LUOYANG CITY IN HAN AND WEI DYNASTIES - Jin Lipeng (International Journal of Innovative Technologies in Social Science, 2020)
The author of this article reviews the architectural style of Luoyang City during the Han and Wei dynasties by studying historical data, analyzes its architectural style characteristics from a historical perspective, and provides some suggestions for later scholars to study Chinese ancient architecture.